Changes in testicular size, echotexture, and arterial blood flow associated with the attainment of puberty in Dorper rams raised in a subtropical climate - Camela, Efigenia S. C. [UNESP]; Nociti, Ricardo P. [UNESP]; Santos, Victor J. C. [UNESP]; Macente, Beatrice [UNESP]; Murawski, Maciej; Vicente, Wilter R. R. [UNESP]; Bartlewski, Pawel M.; Oliveira, Maria Emilia F. [UNESP] (Wiley-Blackwell, 2019)
Contents There is a paucity of information on the relationships of testicular morphology, echotextural attributes, and blood flow dynamics with pubertal development of rams raised in a subtropical climate. Forty-five Dorper rams (24 rams aged 8-11months and 21 rams aged 12-24months) were examined using a portable ultrasound scanner connected to a 7.5-MHz transducer. Computer-assisted analyses of testicular ultrasonograms utilized commercially available Image ProPlus((R)) analytical software. Spectral Doppler scans of testicular arteries were performed immediately after scrotal (B-mode) ultrasonography to determine peak systolic velocity (PSV), end-diastolic velocity (EDV), resistive index (RI=[PSV-EDV]/PSV), and pulsatility index (PI=[SPV-EDV]/mean velocity) of the blood vessels. The length of the testes (9.7 +/- 0.3 compared with 9.0 +/- 0.2cm) and scrotal circumference (33.3 +/- 0.5 compared with 31.8 +/- 0.4cm) were greater (p<0.05) but testicular depth (4.5 +/- 0.1 compared with 4.9 +/- 0.08 cm) was less (p<0.05) in sexually mature compared with peripubertal rams. [Corrections added on 9 Jan 2019 after initial online publication: The testicular size values in the sentence were corrected.] There were no differences (p>0.05) between the two age groups of Dorper rams in blood flow indices of testicular arteries. Mean numerical pixel values (100.5 +/- 4.1 compared with 89.2 +/- 4.8) and pixel heterogeneity (25.6 +/- 0.6 compared with 23.6 +/- 0.5) of testicular parenchyma were greater (p<0.05) in peripubertal than in postpubertal rams. Semen volume was negatively correlated with PI of testicular arteries (r=-0.57, p=0.04). In summary, the attainment of sexual maturity in the rams of the present study was associated with significant changes in testicular length and depth, scrotal circumference, and parenchymal echogenicity/hetrogeneity but not in testicular volume and blood perfusion rates. Testicular artery PI can be used to predict the volume of ejaculate in rams.
Keywords: image analysis; puberty; ram; semen; testis; testosterone; ultrasonography